Papel da proteína P21 de Trypanosoma cruzi na inflamação e na infecção crônica experimental in vivo. - Teixeira, Thaise Lara (2018)
T. cruzi is the etiologic agent of Chagas disease. This protozoan, upon entering the vertebrate host, is able to invade a wide of nucleated cells. For this, it uses secreted proteins that have modulatory activity in the infection. The P21 protein is secreted by T. cruzi and exhibits important biological activity, such as promoting phagocytosis and polymerization of the actin cytoskeleton in host cells. In this study, we discovered other biological activities of P21. Using a model of chronic inflammation (polyester sponge) in murine, we demonstrated that P21 has chemotactic activity, induction of Interleukin-4 production, fibrosis, and inhibition of angiogenesis. We also evaluated chronic T. cruzi infection compared to L. amazonensis infection, also in murine, in the presence of P21. In this case, P21 was able to increase the parasite load of L. amazonensis and, conversely, inhibited the replication of T. cruzi in vivo and in vitro. In addition, we demonstrated that in mice treated with rP21, cardiac tissue exhibited intense inflammatory foci, increased collagen deposition, and inhibition of angiogenesis. From this, in order to inhibit P21, we performed a series of in vitro assays using a synthetic peptide (P1) binding the protein. We have seen that P1 inhibited actin polymerization and the anti -angiogenic activity of P21. In addition, it was able to reduce invasion and induce replication of T. cruzi in macrophages. Therefore, P21 plays an important role in the context of T. cruzi infection and may be a target in therapeutic studies for Chagas' disease.